Fenología del cafeto (Coffea arabica L.) en tres sitios de producción cafetalera de Malacatos, Chaguarpamba y Zapotepamba de la provincia de Loja - Cuenca Cabrera, Edith Alexandra (2020)
The research entitled "Phenology of the coffee tree (Coffea arabica L.) in three coffee production sites of Malacatos, Chaguarpamba and Zapotepamba of the province of Loja", whose objective was to characterize the phenological states of the coffee plant with different climatic conditions, through The use of the amplified BBCH scale (Biologische Bundesanstalt, Bundessortenamt und CHemische Industrie) was carried out within three coffee-growing zones located at an altitude of 900, 1 540 and 1 680 m s.n.m, with temperatures of 18 ° to 23 ° C and annual rainfall of 23 to 156 mm; 10 coffee plants were randomly selected at 5 years of age, choosing three branches from the middle third per plant, with a total of nine samplings at intervals of 20 days. The following variables were evaluated from September 2019 to March 2020: number of leaves, shoots, buds, twigs, flowers and fruits. For the variable flowers, the following codes were used; 53,57,59, 60 and for fruits 70,71, 73, 75, 77, 79, 81. The data on the number of shoots was different between sites, while the number of leaves, flowers and twigs was quite similar; In addition, the biggest difference within each site was the number of reproductive buds and number fruits. During the evaluations, the following averages were recorded in Malacatos: 4.9 shoots, 21.1 leaves, 8.2 buds, 3.1 twigs, 3.0 E57 flowers and 39.6 total fruits, with temperatures of 18 at 22.3 ° C and with rainfall from 24 mm to 156 mm, Chaguarpamba presented the following averages: 2.6 shoots, 17.3 leaves, 23.3 buds, 2.0 twigs, 1.5 flowers in stage 57 and 164.6 total of fruits, with a temperature of 20 to 21.1 ° C and rainfall ranging from 23.3 to 242 mm, finally, Zapotepamba that presented an average of 2.9 shoots, 5.2 leaves, 6, 9 buds, 2.1 twigs, 3.7 flowers in state 57 and total fruit 56.6, presenting a temperature range of 19.5 to 20.8 ° C and with rainfall of 0.9 to 77 mm. In this way, each of the data recorded for flowers and fruits shows the direct influence of climatic factors on each of these variables. Key words: Phenology, climate change, temperature, precipitation.